Islamic Macroprudential Policy to Support Staple Agricultural Sector Financing - Ferry Syarifuddin (Economia Agro-Alimentare)
The study aims to recommend Islamic macroprudential policy instruments to support Indonesia’s staple agricultural sector financing. Delphi-ANP analysis method is used to determine the optimal Islamic macroprudential instruments, which result is supported by meta-analysis and optimum method findings. The results show that Islamic Agricultural Lending to Sector (IALTS) is the optimal instrument to support agricultural sector financing. According to the ANP and optimum method findings, an Islamic macroprudential instrument should meet three criteria i.e., it should be able to increase financing for the agricultural sector, prevent speculative short-term transactions, and internalize systemic risk. Experts emphasized that IALTS have met the criteria to support sustainable growth and stability in the agricultural sector financing. Meta-analysis reveals a positive and significant correlation between agricultural financing and agricultural productivity across countries, which supports the instrument of macroprudential implementation. The government should adopt measures to boost agricultural production through macroprudential policy tools, financing for agriculture from Islamic banks, and policies that ensure inclusive agricultural financing for the benefit of all levels of farmers.